ANALISIS KARAKTERISTIK BENTUK ALIRAN SUNGAI TUNTUNGAN DESA SEI BERAS SEKATA, KECAMATAN SUNGGAL, KABUPATEN DELI SERDANG, SUMATERA UTARA - Lara Anjelita Tarigan (Geography Education Study Program, Universitas Samudra, 2022)
The purpose of this study was to find out how the characteristics of the Tuntungan River flow form in Sei Beras Sekata Village, Sunggal District, Deli Serdang Regency, North Sumatra. The method used in this study is a qualitative method, with direct fieldwork and direct observation in the Tuntungan River, Sei Beras Sekata Village, Sunggal District, Deli Serdang Regency, North Sumatra. The data collection technique used in this study was carried out with the stages of Observation and documentation taking pictures directly in the area and through Google Earth Pro. The results showed that the shape of the Tuntungan watershed has a dendritic river flow pattern, because the flow pattern with river branches resembles a cross-sectional line or leaf reinforcement. The movement of the Tuntungan River flow is a type of turbulence caused by irregular water flows.